How forgiveness relieves anxiety: the role of differentiation of self - Kaleta, Kinga (Journal of beliefs and values, 2023)
Although forgiveness has been found to reduce anxiety, no research to date has examined the actual mechanism. This could be derived from Murray Bowen’s theory and his concept of differentiation of self (DoS). In the present cross-sectional study, we tested a model in which self-differentiation mediates the link between dispositional forgiveness and trait anxiety. The sample was composed of 216 individuals. Polish adaptations of the Heartland Forgiveness Scale, the Differentiation of Self Inventory-Revised, and the State-Trait Anxiety Inventory were used. Results indicated that the three aspects of DoS (emotional reactivity, I-position, emotional cut-off) partially mediated the negative association between total forgiveness and anxiety. Emotional reactivity and emotional cut-off mediated the association between reduced unforgiveness and anxiety while positive forgiveness–anxiety link was mediated by I-position and emotional cut-off. The findings demonstrate that differentiation of self might be a mechanism via which forgiveness reduces anxiety after one has been hurt.